A Career as a Diesel Mechanic - Culp, Jennifer 1985- (New York Rosen Publishing, 2019)
"A book for teens about working as a diesel mechanic."--Provided by publisher.
Powered by diesel: keeping the country running -- What does it take? -- Mechanics in school -- Beginning a career with big engines -- From school to the workplace -- ASE and other certifications.
Includes bibliographical references and index.
Keywords: Diesel motor -- Maintenance and repair; Diesel motor industry -- Vocational guidance